Referendum w opinii elit politycznych III RP - Rachwał, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
This draft was inspired by the intention to describe the attitude of the political elites of contemporary Poland to referendums at the national level. To this end, reference is made to the opinions voiced in the period 1989–2011. Consequently, the analysis spans the experience of twenty two years, which is a sufficient period to identify certain regularities. The surveys conducted indicate that Polish citizens have the right to participate in a referendum, but they do not have a right to referendum, that is to initiate a public vote. This shape of the legal foundations for national referendum is a consequence of the fact that political elites are inclined to apply this institution of direct democracy only provided that it is beneficial to them. Therefore, at the national level there is only a top-bottom referendum (supervised by the political elite). It appears that it contradicts the possibility of treating this institution of direct democracy as equal to representative forms of governance.